Experimental Study of Automatic Weapon Vibrations when Burst Firing - Bien Van VO (Wojskowa Akademia Techniczna, 2021)
The article presents a new approach to finding the dynamic characteristics of automatic weapons, mainly in case of burst firing. The experiments were tested out on a 30 mm AGS-17 grenade launcher mounted on a tripod in the event of a shot. The obtained results are the basis for evaluating the firing stability of an automatic weapon when burst firing, which allows modernising the existing weapons and evaluating similar weapon systems. Furthermore, the outputs can be used to validate a dynamic model of an automatic weapon system mounted on the tripod. The procedure can be used as an example of practical technique and methodology for other weapon systems.
Keywords: Badania broni strzeleckiej